Rastropsha (slyibum marianum) in Surkhandarya soil climatic conditions growth, development and medicinal properties - Jumaev Shuhrat Maksadovich (Zien Journals, 2023)
The botanical description, chemical composition, pharmacological properties, folk medicine significance of the plant Rastropsha have been studied.
Keywords: Olabuta; Botanical description; Pharmacology; antioxidant